Advanced control strategies for partially levitating multi-sector permanent magnet synchronous machines - Wen, Zhuang (2022)
The thesis presents solutions to improve the performance of a partially levitating bearingless permanent magnet synchronous machine with a multi-three-phase winding. A combined winding topology, which consists of three independent three-phase sub-windings, is installed in the stator where each phase contributes to both the suspension force and the motoring torque. This work focuses on control algorithms, including fault-tolerant controls, a current limitation technique, and a current-sharing technique.